Safety and Efficacy of Tofacitinib in Combination With Biologic Therapy for Refractory Crohn's Disease. Issue 2 (4th August 2021) - Lee, Scott David; Singla, Anand; Harper, Jason; Barahimi, Mitra; Jacobs, Jeffrey; Kamp, Kendra J; Clark-Snustad, Kindra Dawn
Abstract: Background: The majority of patients with Crohn's disease (CD) will not achieve endoscopic remission on current therapy. Addition of tofacitinib to biologics may improve remission rates. Methods: We retrospectively assessed safety and clinical and endoscopic effectiveness of off-label tofacitinib and biologics for CD. Results: We identified 19 patients treated with tofacitinib and a biologic for refractory CD between 2017 and 2019. Tofacitinib was added for luminal disease on colonoscopy ( n = 13), luminal disease on capsule ( n = 3), and pyoderma gangrenosum ( n = 3). The mean age was 41.2 years (28–62), mean disease was duration 16.9 years (6–36), and prior exposure to biologics was a median of 4 (1–6). Mean treatment duration was 9.6 months (SD, 3.3). Adverse events (AEs) were reported in 36.8% of patients, most commonly minor infection or CD flare, and no patients had a serious AE; 80.0% ( n = 8) achieved clinical response, and 60.0% ( n = 6) achieved clinical remission based on Harvey-Bradshaw Index. Endoscopic improvement occurred in 54.5% ( n = 6), endoscopic remission in 18.2% ( n = 2), and endoscopic healing in 18.2% ( n = 2) of patients. Mean Simple Endoscopic Score in CD significantly improved from 13.6 ± 5.2 to 6.5 ± 4.0 after treatment ( P < .01). Conclusions: In patients treated with tofacitinib in combination with a biologic, no new safety signals were observed. Combination tofacitinib and a biologic was effective in achieving clinical and endoscopic improvement in some patients with severe, refractory CD, although a larger sample size is needed to further assess the efficacy and long-term safety of this treatment strategy.